Carbon decoupling and economic growth in Africa: Evidence from production and consumption-based carbon emissions - Dagmawe Tenaw (Elsevier, 2021)
This study examines the issue of decoupling between economic growth and carbon emissions in 25 African countries over 1990–2017. The study also assesses the role of international trade on carbon emissions The novelty of this study is that it jointly considers both production-based and consumption-based carbon emissions approaches in the regional decoupling analysis and the corresponding separate effects of exports and imports on the decoupling process. The Common Correlated Effects Mean Group (CCE-MG) and Augmented Mean Group (AMG) estimation techniques which allow for cross-sectional dependence, heterogeneity, endogeneity, and serial-correlation issues are mainly applied for empirical analysis. The findings invariably indicate some evidence of relative decoupling for production-based emissions, as the threshold levels of GDP per capita are located well within the range of data in all estimations, but above the sample average of $3770. In contrast, there is no robust evidence of decoupling for consumption-related emissions. Primary energy intensity and population are found as the main drivers of carbon emissions. Further, exports and imports have insignificant effects on production-based emissions, but significant and offsetting effects on consumption-based emissions. The policy implication of the study, thus, is that the global community and policymakers need to pay close attention to consumption-based carbon emissions in international climate negotiations and target-setting discussions, as production-related emissions alone would be insufficient for decarbonizing economic growth.